Régimen constitucional de la moneda y estabilidad del nivel general de precios en Perú - Rodríguez Cairo, Vladimir (2020)
The constitutional regime of currency is one of the most relevant economic institutions in a country because it institutes an order, model, or monetary system aimed to preserve price stability and, thereby, to generate confidence, security, and certainty in the economy. Thus, this research established the implication of the constitutional monetary regime in the general level of prices and individual wellbeing. The study design was nonexperimental because the variables were not manipulated, retrospective because it was based on secondary data, analytical because it was a bivariate analysis and cross-sectional because the data was obtained at a single moment. Likewise, the scope was correlational because of the degree of relationship between the study variables and explanatory since it was determined by the causality that was established between these variables. The currency was founded as a spontaneous order (merchandise money) and a constructed order (fiduciary money), as well as the legal and economic content of the currency’s constitutional regime. The main result was that monetary stability, in addition to being a fundamental right, is a constitutive commitment that fosters the creation of basic values in society, and its preservation has allowed the purchasing power of the currency to be stable for the last twenty seven years, thus contributing to the well-being of the population. Therefore, price stability has been the most relevant achievement of the current monetary regime.